S antigen specific effector T cell activation detected by cytokine flow cytometry. Issue 5 (1st May 2002) - Morgan, J P; Robins, R A; Dua, H S; Tighe, P J
Abstract : Background/aims: Effector T cell activation is particularly important in the initiation of autoimmune uveitis. This pilot study seeks to demonstrate activation of human peripheral effector T cells in response to the uveitis candidate autoantigen, retinal S antigen (SAg), using cytokine flow cytometry (CFC). Methods: Peripheral blood mononuclear cell (PBMC) suspensions from uveitis patients and controls were stimulated with bovine SAg. Activation responses were detected by CFC. Results: Electronic gating enabled analysis of CD69+, IFN-γ+ CD4+ lymphocytes. An SAg specific response was detectable in four of 13 patients and four of eight controls. Conclusion: SAg specific, peripheral, effector T cell activation can be detected by CFC. Similar levels of responsiveness were seen in patient and control groups. More detailed cytokine profiling may demonstrate functional differences between the groups.